Research on Optimization of Gear Micro-modification based Genetic Algorithm - Gang Lei; Huyin Wang; Ziqian Liu; Yanjun Jiang; Chaochao Chen; Ling Qin; Jiale Chen; Lin Liu; Binxiong Liao (Jixie chuandong)
Taking the noise of a certain DCT transmission as the research object，the noise order of the second gear small throttle acceleration is determined by using whole vehicle testing technology and order analysis method. A Romax rigid-flexible coupling analysis model is established，and the micro-modification parameters originally designed are introduced into the finite element model to conduct the test and simulation analysis of contact spot calibration. It is found that under 20% of the input rated torque，a deflection load appears in the simulation and test contact spot，which provides a correct finite element analysis model for subsequent micro-modification. In order not to affect the requirements of other acceleration conditions，a genetic algorithm is introduced to optimize the micro-modification parameters of the second gear by reducing the peak-to-peak value and load per unit length of the transmission error of the second gear. Considering the requirements of machining accuracy，the optimized micro-shape modification parameters are rounded，and the peak-to-peak value of transmission error and load per unit length of 2-gear small throttle acceleration condition are obtained，which are lower than the original design. The vehicle test data shows that the noise of the second gear is reduced by 11.36% after modification and optimization. Subjective evaluator evaluates that there is no obvious noise in the vehicle under the acceleration condition of the second gear. It shows that the application of genetic algorithm to optimize gear micro-modification has practical engineering guidance significance for reducing transmission error.